MONETARY POLICY INTEREST RATE AT THE CONFLUENCE WITH MACROECONOMIC INDICATORS - Lucian-Ion MEDAR (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
The monetary policy rate is besides a monetary instrument and a monetary policy measure of the central banks. Communication of decisions on the level of official monetary policy rates targets the stability of prices. The confluence between the macroeconomic indicators and the monetary policy rate is the place where the monetary policy measures meet with the main indicators that reflect the state of the economy over a certain period of time. In this paper I will present a reflection on the situation of the main indicators: GDP, inflation and unemployment, as well as the monetary policy rate imposed by the central banks. As a method of research we used the analysis of the mechanism of transmission of monetary policy decisions at the confluence with the main macroeconomic indicators.